New Coronavirus Infection (Covid-19): Clinical and Epidemiological Aspects - V. V. Nikiforov; T. G. Suranova; T. Yu. Chernobrovkina; Y. D. Yankovskaya; S. V. Burova (Архивъ внутренней медицины)
Environmental change, climate warming, population density increase, high migration activity of the population and other factors provoke the emergence and spread of new infections around the world. The emergence in December 2019 of diseases caused by the new coronavirus («coronavirus disease 2019») has already gone down in history as an emergency of international importance. It is known that the most common clinical manifestation of a new infection is pneumonia, and also in a significant part of patients — respiratory distress syndrome. Our article provides a brief analytical review of these temporary guidelines Ministry of Health of the Russian Federation «Prevention, Diagnosis and Treatment of a New Coronavirus Infection (COVID-19)», version 3 (03.03.20) and other published sources. The team of authors expresses the hope that these data will be useful to doctors in providing medical care to patients with a new coronary virus infection, as well as to teachers in preparing students and residents. Source: Ministry of Health of the Russian Federation. Temporary guidelines «Prevention, diagnosis and treatment of new coronavirus infection (COVID-19)», version 4 (27.03.20). Available on: https://static-3.rosminzdrav.ru/system/attachments/attaches/000/049/881/original/COVID19_recomend_v4.pdf